Reproductive Health Needs among Children with Hearing and Visual Impairements at SLB Karya Murni Ruteng , NTT Province - fransiska demang; Claudia Fariday Dewi (Alta Dharma Publisher, 2021)
Children with Special Needs (hearing and visual impairments) will experience the same sexual development, confusion, and sexual urges as some normal children. However, access to information to obtain knowledge about reproductive health is still lacking due to their limitations. It is happened because of the lack of attention and support from the government and the general public. It is necessary to identify reproductive health needs so that health service activities can be right on target and increase the reproductive health services in this group. This study aims to identify the reproductive health needs of children with special needs (hearing and visual impairments) in SLB Karya Murni Ruteng. This research is qualitative research with a phenomenological study approach. This research was conducted at SLB Karya Murni Ruteng from May to August 2020. Participants in this study were six hearing impairments children and seven visual impairments. The principle of sampling in qualitative research is to achieve data saturation means there are no new themes that showed up. The participants in this study were 13 people because they had received data saturation. Research data collection was carried out through Focus Group Discussion (FGD) on hearing impairments children, assisted by their teacher to translate the sign language proposed by the researcher. And for the visual impairment children, the research data were collected through in-depth interviews. Researchers used interview guidelines to assist researchers in asking research-oriented questions. Analysis of the data used in this study using content analysis. The analysis provides in narrative form started from coding each informant's statement that is relevant to the research, categorizing, and producing themes under the research objectives. The validated data carried out by triangulation of sources that confirming the answers with related parties so that there was the suitability of the answers given to the informants. The source of triangulation was taken from the teachers and principals of Karya Murni's SLB, who were always with them both at school and in the school dormitory. The results of the study explained that most children with special needs did not have a comprehensive understanding of Reproductive Health. The role of parents and educators is still not maximal in giving the understanding of reproductive health to children with special needs. Health services, especially reproductive health, which is currently being echoed by the central and regional governments, have not touched people with special needs